2003
DOI: 10.1002/art.11340
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Raynaud's phenomenon in children ages 12–15 years: Prevalence and association with other common symptoms

Abstract: Objective. Although Raynaud's phenomenon (RP) in adults is frequently reported as having been present since childhood, there have been no studies on the prevalence of RP in children. This study was undertaken to ascertain the prevalence of RP in children ages 12-15 years and to determine whether, as with other commonly reported symptoms, there were any associations with adverse psychosocial factors. Methods. A previously validated selfadministered RP questionnaire was distributed to 903 children ages 12-15 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 17 publications
1
16
0
2
Order By: Relevance
“…Sixty-seven per cent of the studies involved participants recruited in a community-based setting. The majority of studies were conducted in Europe (18) 6 9 19 22 24 26 27 29 30 32 33 35–37 39 41–43 or the USA (10), 7 8 10 11 20 21 23 38 40 44 however, other countries of origin included Japan (2), 25 28 New Zealand (1) 34 and Israel (1). 45 One comparison study included participants from the USA and France.…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-seven per cent of the studies involved participants recruited in a community-based setting. The majority of studies were conducted in Europe (18) 6 9 19 22 24 26 27 29 30 32 33 35–37 39 41–43 or the USA (10), 7 8 10 11 20 21 23 38 40 44 however, other countries of origin included Japan (2), 25 28 New Zealand (1) 34 and Israel (1). 45 One comparison study included participants from the USA and France.…”
Section: Resultsmentioning
confidence: 99%
“…In both primary and secondary RP, monophasic color changes are more common than biphasic or triphasic changes (). No seasonal or psychosocial factors have been shown to influence the reporting of RP symptoms, at least in older children (). In children ages 12–15 years, a relationship with pain including in the arm/shoulder region has been reported ().…”
Section: Capillaroscopy In Children With Rpmentioning
confidence: 99%
“…No seasonal or psychosocial factors have been shown to influence the reporting of RP symptoms, at least in older children (). In children ages 12–15 years, a relationship with pain including in the arm/shoulder region has been reported (). Pediatricians need to be aware that while RP is not uncommon (and is being increasingly recognized) in children and is usually benign primary (idiopathic) RP, RP may be the presenting feature of an underlying CTD.…”
Section: Capillaroscopy In Children With Rpmentioning
confidence: 99%
“…In the U.K., a study of 720 children aged 12 to 15 years found a prevalence of 12 % in boys and 18 % in girls using a selfadministered questionnaire, whereas in the same population a prevalence of 8.3 % for adult men and 17.6 % of adult women was published [33,34].…”
Section: Primary Raynaud's Phenomenon In Childrenmentioning
confidence: 99%